Treatment of Spasticity Due to Multiple Sclerosis with Sativex®: Who Benefits Most? Three Case Reports - Mercanti, Stefania Federica De; Fraccalini, Thomas; Lavorgna, Luigi; Clerico, Marinella (Archives of Clinical and Medical Case Reports, 2021)
The evidence available suggests that cannabinoid-based products improve spasticity, chronic pain, and bladder dysfunction, which are common symptoms in more than 50% of multiple sclerosis (MS) patients. In this paper we present three cases of patients with progressive or relapsing forms of MS, with different severity, duration, and with various degrees of hypertonia and or bladder dysfuction, treated with nabiximols (Sativex®). Nabiximols was administered as an oral spray to reduce MS-associated hypertonia. The results show the efficacy of the therapy in MS patients with moderate to severe spasticity and resistant or intolerant to common myorelaxants drugs. In conclusion, nabiximols proves to be an effective treatment, easy to administer, even in patients with motor disabilities affecting the hands, and without important side effects.